Conceptualising backlash politics: Introduction to a special issue on backlash politics in comparison - Karen J. Alter; Michael Zürn (British Journal of Politics and International Relations, 2020)
Despite the widespread sense that backlash is an important feature of contemporary national and world politics, there is remarkably little scholarly work on the politics of backlash. This special issue conceptualises backlash politics as a distinct form of contentious politics. Backlash politics includes the following three necessary elements: (1) a retrograde objective of returning to a prior social condition, (2) extraordinary goals and tactics that challenge dominant scripts, and (3) a threshold condition of entering mainstream public discourse. When backlash politics combines with frequent companion accelerants – nostalgia, emotional appeals, taboo breaking and institutional reshaping – the results can be unpredictable, contagious, transformative and enduring. Contributions to this special issue engage this definition to advance our understanding of backlash politics. The special issue's conclusion draws insights about the causes and dynamics of backlash politics that lead to the following three potential outcomes: a petering out of the politics, the construction of new cleavages, or a retrograde transformation. Creating a distinct category of backlash politics brings debates in American politics, comparative politics, and international relations together with studies of specific topics, facilitating comparisons across time, space, and issue areas and generating new questions that can hopefully promote lesson drawing.
Keywords: 300; backlash politics; contestation; emotional politics; taboo breaking; nostalgia; public discourse; retrograde